THE ANALYSE OF STUDENTS ABILITY IN WRITING PERSONAL LETTER AT XI CLASS OF SMA NEGERI 1 BADAR - Putri Sarmadi; Raja Fauziah; Muhammad Tahir (STKIP USMAN SAFRI KUTACANE, 2022)
The purpose of this study is to analyse the ability of respondents in writing personal letters in terms of aspects: 1) content, 2) composition of content, 3) sentence structure, 4) vocabulary, and 5) mechanics or spelling. The research method used is a qualitative method with the population of all students of Class XI SMA Negeri 1 Badar amounting to 152 respondents. Until in this study 25% of the population was as many as 38 respondents, with a random sample technique. Data collection is done by giving tests to respondents making personal letters. Analysis of the use of scale and using the mean equation. The results of the analyse of students ability in writing personal letter at XI class of sma negeri 1 Badar. it is known that the ability to write look after analyzed by using categories, 10 respondents get a good category with a percentage of 26%, 28 of the respondents who get the category enough with a percentage of 74%. On average, the ability to write a personal letter to the overall show on the criteria enough. The respondents personal letter writing ability score is on the qualification with the acquisition of the respondents overall average score of 68.11 data analysis results of each aspect can be seen from the average value of each aspect assessed in writing a personal letter, namely in the aspect: Result of content 21,87obtaining enough categories, organisational aspects of the content 13,42 with enough criteria, aspects of sentence structure 14,03 with good criteria, aspects of vocabulary 1o on Good criteria, and aspects of mechanics or spelling 8,79 with enough criteria.